2019
DOI: 10.3390/catal9090759
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Synthesis of ZrOx-MnCO3/Graphene Oxide (GRO) Nanocomposites for the Oxidation of Alcohols using Molecular Oxygen under Base Free Conditions

Abstract: Graphene and its nanocomposites are showing excellent potential in improving the catalytic performances of different materials. However, the synthetic protocol and its form, such as graphene oxide (GRO) or highly reduced graphene oxide (HRG), influence the catalytic efficiencies. Here, we present, a facile synthesis of graphene oxide (GRO) and ZrOx-MnCO3-based nanocomposites [(1%)ZrOx–MnCO3/(x%)GRO] and their outcome as an oxidation catalyst for alcohol oxidation under mild conditions using O2 as a clean oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…On the other hand, copper-based catalysts have also been broadly employed for several conversions, such as CO oxidation [23], benzene oxidation [24], and the hydroxylation of benzene [25]. In order to replace the noble metals, cheaper alternatives are being probe ing these noble metals with cheaper transition metals for a variety of chemic [11][12][13][14]. One such transition metal is Zn, and zinc-based catalysts have been w for various conversions such as decomposition of nitrous oxide [15], oxidati [16], hydrocarbon oxidation [17], dye degradation [18], and preparation of a 22].…”
Section: Of 14mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, copper-based catalysts have also been broadly employed for several conversions, such as CO oxidation [23], benzene oxidation [24], and the hydroxylation of benzene [25]. In order to replace the noble metals, cheaper alternatives are being probe ing these noble metals with cheaper transition metals for a variety of chemic [11][12][13][14]. One such transition metal is Zn, and zinc-based catalysts have been w for various conversions such as decomposition of nitrous oxide [15], oxidati [16], hydrocarbon oxidation [17], dye degradation [18], and preparation of a 22].…”
Section: Of 14mentioning
confidence: 99%
“…In order to replace the noble metals, cheaper alternatives are being probed by replacing these noble metals with cheaper transition metals for a variety of chemical reactions [11][12][13][14]. 2…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al [17] have used samples for an average nanoparticle that size of 50 nm. The turpentine fluid process is the good mass ratios between 5 to 25%, followed by the fluid nanoparticles by Adil et al [18], Ajay Kumar et al [19]. It has been used in a magnetic stirrer, which is miscellaneous in fluid nanoparticles way of the turpentine fluid and disturbed to the particles as followed on 2 hours, then speeds of constant for 1000rpm.…”
Section: The Design Of Suitable Materials For Fluid Nanoparticlesmentioning
confidence: 99%
“…Our earlier studies demonstrated the preparation of numerous metal-based nanocatalysts and their graphene nanocomposites and investigated their catalytic performances towards oxidation of alcohols [39][40][41]. In one such study, we demonstrated the promoting effect of zinc oxide NPs in the MnCO 3 , i.e., (1%) ZnO-MnCO 3 nanocatalyst which afforded superb activity for aerial dehydrogenation of alcohols in the presence of O 2 .…”
Section: Introductionmentioning
confidence: 99%